Analisis Pengaruh Bimbingan Karir, Lingkungan Keluarga, Dan Efikasi Diri Terhadap Kesiapan Kerja Mahasiswa - Aprillia Suryani Pujiastuti; Bayu Kurniawan; Setyorini, Noni (Fakultas Ekonomi dan Bisnis Universitas PGRI Semarang, 2023)
This study aims to test and analize the effects of career guidance, family environment, and self-efficacy on work readiness undergraduate. The population in this study is undergraduates on the faculty Management study program of the Economi and Business Uniniversity of PGRI Semarang class of 2019, there were as many as 161 students as respondents. The sampling technique used is Purposive Sampling technique with Likert Scale measurement. This study uses quantitative methods and uses primary data by distributing questionnaires to undergraduate of Management of the FEB, class of 2019. Data is processed through the SPSS version 26 for windows program. Based on research using a t-test, the results obtained that career guidance have a positive and significant influence on work guidance, the results obtained that family environment have a positive and significant influence on work guidance, and the results obtained that self-efficacy have a positive and significant influence on work guidance. The results of the determination coefficient test obtained a value from the Adjusted R Square of 39,7%, this can be interpreted to mean that career guidance, family environment, and self-efficacy can explain work readiness of undergraduate of Management of the FEB, class of 2019.